Vliyanie adaptatsii i deistviyu reglamentirovannoi gipobaricheskoi gipoksii razlichnoi prodolzhitelnosti na organizm sportsmenov, cpetsializiruyushchikhsya v vidakh sporta na vynoslivost - Nikonorov, A. A.; Tverdochlib, V. P. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The purpose of the research was to study the dependence of effects of acclimatization from the duration of the action of periodic regulated hypoxia. 50 elite athletes specialized in endurance kinds of sports (track&field athletics, ski races) have taken part in the research. All the athletes were divided into 2 similar groups, each of which had passed a 4-week course of adaptation to the action of regulated hypoxia, distinguished only in time influence: 1 group - stay in the vacuum chamber for 1 hour; 2 group - for 3,5 hours. The course of hypoxia influence to the second group was accompanied by the essential downstroke of an expressiveness of a lactacidemia after carrying out a standard exercise load - 500-meter running and after 1 min. of rest - 1000-meter running for set time.